If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + -4z = -15 Solving -3 + -4z = -15 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -4z = -15 + 3 Combine like terms: -3 + 3 = 0 0 + -4z = -15 + 3 -4z = -15 + 3 Combine like terms: -15 + 3 = -12 -4z = -12 Divide each side by '-4'. z = 3 Simplifying z = 3
| 9x-6=12x-3x | | 3(-2x-1)=2x+5 | | 4(1+5g)= | | 4x+12+2x= | | 4(1+5g)=Submit | | (5x-2)+(2x+8)+90=180 | | 11j-6j+4j=18 | | 7(4p+1)= | | 2x^5=130 | | 2(1+3n)= | | 5(2+5h)= | | 4x-5=-x-5 | | 135x=4 | | 8m-29=59 | | 4x+12+3x= | | X=y-35 | | 3q+5q=48 | | 3(x+7)+6x=9x-21 | | 4x+8x^2=3 | | 15x=2.50 | | -28=3+8(n+6) | | 4(-2x+3)=-6y | | 15b=2.50 | | 15-6x=-3x+10 | | 3x+1=4x+2-x | | 3x+42+4x+140=-21 | | 63-x/.4 | | -9=0.16666666666z-11 | | Z/4=-8 | | -x+7=-4x-5 | | -15x=-5x+10 | | -15x=-5a+10 |